Cognitive justice and environmental learning in South African social movements - Burt, Jane Caroline (Rhodes University, Faculty of Education, Department of Environmental Learning Research Centre)
This thesis by publication is an applied study into transformative learning as an emancipatory practice for water justice. It is guided by the core research question: How can cognitively just learning be an activist practice in social movements working towards water justice? To address this question, I use the applied critical realist approach which makes use of three moments of moral reasoning which are very similar to the approach adopted in the learning intervention that is the focus of this research. These three moments are: Diagnose, Explain, Act "“ sometimes known as the DEA model (Bhaskar, 2008, 243; Munnik & Price, 2015). The research object is the Changing Practice course for community-based environmental and social movements. The course was developed and studied over seven years, starting from the reflexive scholarship of environmental learning in South Africa, particularly the adult learning model of working together/working away developed through the Environmental Education Association of Southern Africa in partnership with the Environmental Learning Research Centre at Rhodes University (Lotz-Sisitka & Raven, 2004). We (the facilitators/educators) ran the Changing Practice course three times (2012-2014; 2014-2016; 2016-2018), in which I generated substantive data which forms the empirical base on which this study was developed. We found the concept of cognitive justice (Visvanathan, 2005; de Sousa Santos, 2016) to be a powerful mobilizing concept with which to carry out emancipatory research and learning, in three ways. First, it brought together a group of researchers, activists and practitioners from different organizations to work on how to strengthen the role of civil society in monitoring government water policy and practice (Wilson et al., 2016). Second, within the Changing Practice course itself, it became a principle for guiding learning design and pedagogy as well as a way of engaging in dialogue with the participants around the politics of knowledge, exclusion and inclusion in knowledge production, systems of oppression and multiple knowledges (Wilson et al., 2016; Burt et al., 2018). Thirdly, the participants' change projects (the applied projects undertaken during the 'working away' phase between course modules), allowed participants to draw on different knowledge systems, which they learnt to do in the 'working together' modules, and to address cognitive justice concerns linked to environmental justice. The change projects also challenged our learning pedagogy by raising contradictions in the course's approach to learning that needed to be transformed in order for our pedagogy to be more cognitively just. Throughout this thesis I argue that the work of cognitive justice deepens the connections between people, institutions and structures, particularly in relation to transformative learning. Our intention was to identify and critique structures and ideologies that perpetuated oppressive relations, and then to identify and enact the work needed towards transforming these relations. This is why I often refer to cognitive justice as a solidarity and mobilizing concept, and I use the term cognitive justice praxis to mean the reflection and actions that are needed to enact cognitive just learning. The facilitators and participants of the Changing Practice course worked to remove the layered effects of oppression both in the practice of water justice and in the learning process itself. We worked, however imperfectly, with a caring, collectively-held ethic towards each other and the world. Using the DEA model I applied the critical realist dialectic to analyse contradictions and generate explanations through four articles as reflexive writing projects (See Part 2 of this thesis). I used the critical realist dialectic both to reveal contradictions, investigate how these contradictions have come to be, and to generate alternative explanations and action to absent them. Through this research I identified four essential mechanisms for cognitively just environmental learning: care work, co-learning, reflexivity and an interdisciplinary approach to learning scholarship as learning praxis. The essential elements that made the Changing Practice course so effective were the working together/working away design, the encouraging of participants to make the change project something they were passionate about, and the situating and grounding of the Changing Practice course within a social movement network. We were able to show that for academic scholarship to contribute meaningfully to cognitively just learning praxis, it needs to be collaborative and reflexive, and start from the embodied historical and contextual experience of learning as experienced and understood by participants on the course. This demanded an interdisciplinary approach to work with contradictions in learning practice, one that could take into consideration different knowledges and knowledge practices beyond professional disciplines. Both social movement communities and scholarly communities have valuable knowledge to offer each other. As argued in article one, rather than a lack of knowledge, what more often limits our emancipatory action are factors that prevent us from coming closer together. (Burt et al, 2018) This research revealed that social movement learning towards water justice is multi-level care work, the four levels being: individual psychology, our relations with others, our relations with structures such as our social movements, and our relations with the planet. When such care work attains self- reflexivity, practice-reflexivity, co-learning and collective scholarship, it is able to absent the contradictions that inhibit cognitive justice. This thesis is a record of our attempts to learn how to achieve this.
Keywords: Transformative learning; Water security -- South Africa; Environmental education -- South Africa; EEASA (Organization); Civil society -- South Africa; Water justice; Cognitive justice